2000
DOI: 10.1002/1521-4095(200011)12:22<1655::aid-adma1655>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting (Conjugated) Polymers as Materials for Solid-State Lasers

Abstract: Light-emissive polymers are outstanding laser materials because they are intrinsically ª4-levelº systems, they have luminescence efficiencies higher than 60 % even in undiluted films, they emit at colors that span the visible spectrum, and they can be processed into optical quality films by spin casting. The important materials issues are reviewed and the prospects for making polymer diode lasers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
138
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 29 publications
1
138
0
1
Order By: Relevance
“…This last symptom can lead to less-than-optimized device properties because of, for example, metal-induced quenching of the light emission [17,18] and doping-induced short-circuit formation. [19] Even though the operational mechanism of LECs has been the subject of many studies and considerable understanding has been accumulated, [1,2,[20][21][22][23][24][25][26][27][28][29] many key properties remain to be established; for example, what causes the limited operational lifetime and the off-center emission zone, and what are the doping concentrations and the doping gradients in the p-type and n-type doped regions?…”
Section: Introductionmentioning
confidence: 67%
“…This last symptom can lead to less-than-optimized device properties because of, for example, metal-induced quenching of the light emission [17,18] and doping-induced short-circuit formation. [19] Even though the operational mechanism of LECs has been the subject of many studies and considerable understanding has been accumulated, [1,2,[20][21][22][23][24][25][26][27][28][29] many key properties remain to be established; for example, what causes the limited operational lifetime and the off-center emission zone, and what are the doping concentrations and the doping gradients in the p-type and n-type doped regions?…”
Section: Introductionmentioning
confidence: 67%
“…[1] They are promising materials for use in electroluminescent displays, [2,3] solar cells, [4] sensors, [5,6] thin-film organic transistors, [7] lasers [8] and light-emitting electrochemical cells. [9] However, the stability of these materials under operating conditions needs improvement if they are to be widely used in real products.…”
Section: Introductionmentioning
confidence: 99%
“…[19] The average refractive index n average for wave propagation perpendicular to the grating lines will be between the index of the nonilluminated polymer (n pristine ) and the index of a flood-illuminated film (n illuminated ), where n illuminated > n pristine as a result of the SCN-NCS photoisomerization. It has been demonstrated that changing the refractive index between these limits does not strongly alter the emission pattern (vide supra).…”
Section: Full Papermentioning
confidence: 99%